2012
DOI: 10.1186/1472-6920-12-120
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of contact-based education for reducing mental illness-related stigma in pharmacy students

Abstract: BackgroundA strategy for reducing mental illness-related stigma in health-profession students is to include contact-based sessions in their educational curricula. In such sessions students are able to interact socially with a person that has a mental illness. We sought to evaluate the effectiveness of this strategy in a multi-centre study of pharmacy students.MethodsThe study was a randomized controlled trial conducted at three sites. Because it was necessary that all students receive the contact-based session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 25 publications
8
95
0
1
Order By: Relevance
“…25 Energetic efforts are being carried out, in other nations, to reduce stigma in an effort to identify and treat mental health problems at the earliest. 26 It is probably time, the Armed Forces of this country also take suitable measures on a war footing, to reduce stigma among the mentally ill and their caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…25 Energetic efforts are being carried out, in other nations, to reduce stigma in an effort to identify and treat mental health problems at the earliest. 26 It is probably time, the Armed Forces of this country also take suitable measures on a war footing, to reduce stigma among the mentally ill and their caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of consumer educators to pharmacy training significantly improves pharmacy student attitudes towards mental illness above standardized pharmacy mental health training. 22,25,48 Nguyen et al compared a face-to-face consumer educator intervention with film based interventions and found that both interventions had an equally positive impact on key items relating to MHS. 46 The current study showed significant improvements in stigma perceptions without the use of consumer educators, but through role-playing, active-learning exercises, and patient videos.…”
Section: Discussionmentioning
confidence: 99%
“…9 Contact-based education has become one of the most promising practices in the field of anti-stigma intervention 10 and one that is central to the OM approach to stigma reduction. 11,12 However, note that interpersonal contact is typically directed toward reducing public stigma, not personal experiences of stigma. Our findings indicate that the odds of being stigmatized are similar, whether or not one has had contact with people with a mental illness.…”
Section: Discussionmentioning
confidence: 99%